Different Risk Factors Between Disruptive Behavior Disorders and ADHD in Northern Finland Birth Cohort 1986. (September 2017) - Nordström, Tanja; Hurtig, Tuula; Rodriguez, Alina; Savolainen, Jukka; Rautio, Arja; Moilanen, Irma; Taanila, Anja; Ebeling, Hanna
Objective: To examine different risk factors between disruptive behavior disorders (DBD) and ADHD or combined DBD and ADHD.Method: The study population was derived from the Northern Finland Birth Cohort 1986. Psychiatric diagnoses were defined from the Schedule for Affective Disorders and Schizophrenia for School-Age Children–Present and Lifetime Version (K-SADS-PL) interview. The study sample was divided into four groups—people with DBD ( n = 44), with ADHD ( n = 91), with both ( n = 72), and without either ( n = 250)—to evaluate the different risk factors behind these disorders.Results: After adjusting with possible confounding factors, female gender and paternal admittance to inpatient psychiatric care increased the odds that an adolescent was having DBD. Childhood hyperactivity symptoms increased the odds of having ADHD and childhood hyperactivity symptoms and scholastic impairment increased the odds of having both disorders.Conclusion: Our study indicates DBD and ADHD have clearly different risk factors, and the impact of the paternal factors on DBD should be noted more than has been before.